Urgensi Terbitnya PMA No.73 Tahun 2022 bagi Pondok Pesantren - Siti Ratnawati; Saeful Bahri (Journal on Education, 2024)
This article will answer an important issue about the urgency of the mention of Minister of Religion Regulation Number 73 of 2022 concerning the Prevention and Handling of Sexual Violence for pondok pesantren, considering that the number of cases of sexual violence that have occurred in pondok pesantren lately has made pondok pesantren begin to improve. This study aims to reveal the urgency of issuing regulations on the prevention and handling of sexual violence contained in Minister of Religion Regulation for pondok pesantren. According to the focus of the problem studied, this study uses normative legal methods (legal researh) which are analyzed with normative prescription categories. The results of his research show that, the urgency of the issuance of Minister of Religion Regulation 73 of 2022 for pondok pesantren can be used as: (1) a means of controlling kyai relations with students, (2) a form of guidance and supervision of the Ministry of Commerce, (3) a means to protect themselves by developing a sex education curriculum.